MEKANISME AKSES MASYARAKAT ADAT DALAM PEMANFAATAN SUMBERDAYA ALAM (Studi Kasus di Kasepuhan Karang Desa Jagaraksa Kecamatan Muncang Kabupaten Lebak Provinsi Banten) - Komaratulloh, Putuh; Susdiyanti, Tun; Salampessy, Messalina L (Universitas Nusa Bangsa, 2019)
Forest access is the ability to derive beneï¬ts from things. The purpose of this study is to analyze access mechanism (the right and the structure of access mechanism) the society of law force in the benefit natural resources in the Customary Forest Kasepuhan Karang. This study was held in Kasepuhan Karang Jagaraksa Viilage in November 2018 to January 2019 with observation method which is case study where the data was collected through interview and observation, data analysis conducted with likert scale as well. The result of research showed that the benefit of access natural resources was decided by custom law to the society of Kasepuhan Karang who has the heritage of right to organize the natural forest. Attribute of right based property to the society based on the natural law which is used for the interest of benefit of the society or people who lives around leuweung garapan territorial.